2019
DOI: 10.1016/j.clim.2018.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity-associated intronic SNP (rs2281808) detected by a simple phenotypic assay: Unique case or broader opportunity?

Abstract: Multiple genome-wide association studies have shown that the single-nucleotide polymorphism (SNP) rs2281808 TT variant, present within the signal regulatory protein gamma (SIRPG) gene, is associated with autoimmune diseases, such as type 1 diabetes. SIRPγ is the only SIRP expressed on T cells. The role of SIRPγ in human T-cells or the effect of the TT variant are poorly understood. In this short report, we demonstrate the rather unusual finding that this intronic SNP is associated with a reduction of SIRPγ exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…SIRPγ staining on the T-cells of HD and T1D subjects has already been published before [8,11]. Representative staining of SIRPγ on T-cells of RRMS subjects including low vs. high SIRPγ gates is shown in Fig 2A. We found that overall SIRPγ expression on T-cells of RRMS and T1D patients was significantly lower than T-cells from HD irrespective of the rs2281808 genotype.…”
Section: Sirpγ Expression In Autoimmunity Is Regulated Outside Of Thesupporting
confidence: 56%
See 1 more Smart Citation
“…SIRPγ staining on the T-cells of HD and T1D subjects has already been published before [8,11]. Representative staining of SIRPγ on T-cells of RRMS subjects including low vs. high SIRPγ gates is shown in Fig 2A. We found that overall SIRPγ expression on T-cells of RRMS and T1D patients was significantly lower than T-cells from HD irrespective of the rs2281808 genotype.…”
Section: Sirpγ Expression In Autoimmunity Is Regulated Outside Of Thesupporting
confidence: 56%
“…SIRPγ staining on the T-cells of HD and T1D subjects has already been published before [ 8 , 11 ]. Representative staining of SIRPγ on T-cells of RRMS subjects including low vs. high SIRPγ gates is shown in Fig 2A .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we hypothesize that T1D-associated SNPs in the SIRPG locus contribute towards the decrease of SIRPγ expression on T cells and NK cells, potentially disrupting CD47 signaling and the downstream regulation that constrains the activation and proliferation of these subsets ( Figure 2B ). The impacts of T1D-associated SIRPG SNPs on T cell phenotype have been studied at the polyclonal level, but these observations must be validated in autoreactive islet-specific T cell clones ( 6 , 7 ). SIRPγ low CD8 + T cells isolated from healthy human donors demonstrated an effector gene signature characterized by increased TBX21 , EOMES , IFNG , and GZMB expression, and possessed lower activation thresholds, determined through anti-CD3 titration in vitro , as compared to SIRPγ high CD8 + T cells ( 6 ).…”
Section: Structural Features and Signaling Pathways Of Sirps:cd47mentioning
confidence: 99%
“…Among these variants, those associated with SIRPG (signal regulatory protein gamma), which encodes the receptor-like transmembrane protein SIRPγ, have been proposed to modulate T cell and natural killer (NK) cell activation ( 5 7 ). SIRPG contains two SNPs associated with risk for T1D ( 5 , 8 12 ): rs2281808 [C>T, intronic, minor allele frequency (MAF): 0.27, odds ratio (OR): 1.11] and rs6043409 (G>A, Ala263Val, MAF: 0.20, OR 1.13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation